GAGASAN PEMIDANAAN TERHADAP PEKERJAAN TUKANG GIGI DALAM TINDAK PIDANA MALPRAKTIK DI INDONESIA DITINJAU DARI TEORI PEMIDANAAN - Denia Nabilah Orienza; Evi Deliana; Erdiansyah Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In Indonesia, the number of dental artisans who are members of variousassociations such as the Independent Dental Artisans Association (ASTAGIRI),Indonesian Dental Artisans Association (ITGI), Indonesian Dental Artisans Union(PTGI), Indonesian Dental Artisans Group (HITGI), Indonesian Dental ArtisansForum (FTGI), and Dental Artisans Forum (FPG) is approximately 75,000individuals.This research can be classified as normative legal research, whichexamines the legislation related to the legal theories that are the focus of thestudy. The approach used is qualitative analysis, collecting data from books,journals, and other scholarly works relevant to this research. Primary andsecondary legal sources are utilized as data sources.The conclusion drawn from the research is as follows. Firstly, the urgencyof criminalizing dental artisans in cases of dental malpractice in Indonesia isbased on past cases experienced by victims of dental artisans, as well as illegaldental practices that exceed their authority. Actions are only subject toadministrative sanctions, such as warnings and license revocation. However, theurgency lies in permits and still make mistakes or engage in malpractice shouldbe subject to criminal punishment. The ambiguity of the current provisionnecessitates further study, criminal law reform, and more specific regulations toenable the criminalization of dental artisans. Secondly, the idea of criminalizingdental artisans in cases of dental malpractice in Indonesia was initially regulatedunder Article 78 of the Medical Practice Act.However, the Constitutional Court declared the criminalization of dentalartisans unconstitutional. The wording of Article 78 should be read as follows: